Risks and Rewards: Assessing the Effectiveness and Safety of Classical Invasive Plant Biocontrol by Arthropods. (4th April 2019) - Havens, Kayri; Jolls, Claudia L; Knight, Tiffany M; Vitt, Pati
Abstract: The use of biocontrol agents has been promoted as a relatively safe, efficient, and environmentally friendly alternative to chemical or mechanical control of invasive plant species. However, these agents may not be effective or may have unacceptable nontarget effects on desirable plant species. Although two recent meta-analyses conclude that biocontrol of weeds is effective (Clewley et al. 2012) and that nontarget impacts are rare and minimal (Suckling and Sforza 2014), we found that these conclusions were overstated on the basis of our review of the same literature. Most studies were either data deficient or were not designed to effectively assess biocontrol agent impact on fitness components of targeted weeds and on nontargeted plant species. We call for more rigorous experimental design and monitoring for biocontrol projects in order to obtain the quantitative data needed to make informed decisions about the risks and rewards of invasive plant biocontrol.